Silent Counterattack: The Impact of Workplace Bullying on Employee Silence - Liu, Xiwei; Yang, Shenggang; Yao, Zhu (Frontiers in Psychology, 2020)
The purpose of this paper is to explore the relationship between workplace bullying (WB) and employee silence (ES) as well as its mechanism. This paper collects data from 322 employees of three Chinese enterprises in two waves, with a 2-month interval between the two waves. Moreover, this paper uses confirmatory factor analysis, Bootstrapping mediation test, simple slope test and other methods to verify the hypothesis. We find that: (1) WB is positively correlated with ES; (2) Psychological safety (PS) and affective commitment mediated the relationship between WB and ES, respectively, and these two variables have a chain mediating effect in the above relationship; (3) Forgiveness climate moderates this chain mediating effect by weakening the negative impact of WB on PS. Our findings can effectively guide organizations to timely adjust their management style, pay attention to employees’ cognitive and emotional resources, and formulate some measures to curb WB in organizations.